2011
DOI: 10.1093/icesjms/fsr027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of planktonic foodweb structure on a system's capacity to support pelagic production: an inverse analysis approach

Abstract: Marquis, E., Niquil, N., Vézina, A. F., Petitgas, P., and Dupuy, C. 2011. Influence of planktonic foodweb structure on a system's capacity to support pelagic production: an inverse analysis approach. – ICES Journal of Marine Science, 68: 803–812. Coupled plankton/small pelagic (SP) fish systems were analysed to assess how foodweb structure influences the export of carbon to pelagic fish during the spring bloom in the Bay of Biscay. The investigation of carbon export flows through inverse analysis was supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 43 publications
1
10
1
Order By: Relevance
“…For instance, Plounevez and Champalbert (1999) already suggested that feeding efficiency in E. encrasicolus would be more related to zooplanktonspecific composition than to zooplankton abundance, even if the results of our study cannot confirm or invalidate this hypothesis. Marquis et al (2011) also reported that small pelagic fish only represent 30 % of the total predation on the mesozooplanktonic compartment in coastal stations in the Bay of Biscay (from spring data), and 60 and 65 % at the mid-shelf and the slope stations, respectively. These authors suggested that a large fraction of the mesozooplankton production would be then available for other planktivorous organisms such as suprabenthic zooplankton (euphausiids and mysids) or macrozooplankton (medusa or large tunicates) in the Bay of Biscay .…”
Section: Linking Resource Variability and Feeding Patterns Of Sardinementioning
confidence: 93%
“…For instance, Plounevez and Champalbert (1999) already suggested that feeding efficiency in E. encrasicolus would be more related to zooplanktonspecific composition than to zooplankton abundance, even if the results of our study cannot confirm or invalidate this hypothesis. Marquis et al (2011) also reported that small pelagic fish only represent 30 % of the total predation on the mesozooplanktonic compartment in coastal stations in the Bay of Biscay (from spring data), and 60 and 65 % at the mid-shelf and the slope stations, respectively. These authors suggested that a large fraction of the mesozooplankton production would be then available for other planktivorous organisms such as suprabenthic zooplankton (euphausiids and mysids) or macrozooplankton (medusa or large tunicates) in the Bay of Biscay .…”
Section: Linking Resource Variability and Feeding Patterns Of Sardinementioning
confidence: 93%
“…The high biomass areas such as along the French and Galician coasts still appear highly productive, but in addition, the shelf break is also more productive when compared to the midshelf, which is more conspicuous again over the French shelf. This is partly due to bathymetry, which tends to lower the values in coastal areas after vertical integration as compared to offshore deeper waters, but is also explained by differences in size structure of the zooplankton and underlying primary production (Marquis et al, 2011). The mid-shelf, with the flattest slopes and relatively large zooplankton, is estimated as less productive, even if the biomass seems close to the one over the slope.…”
Section: Productivity and Trophic Controlmentioning
confidence: 98%
“…Within the size range of mesozooplankton (0.2-2 mm ESD), steeper slopes are generally related to lower efficiency of the matter flux, potentially with top-down control and a fewer number of trophic levels, whereas flatter slope areas are associated with efficient transfer under bottom-up control and a higher number of trophic levels (Zhou, 2006;Basedow et al, 2010;Marcolin et al, 2013). So, even if more productive, coastal areas (especially plumes) and to a lesser extent shelf break habitats may have a low transfer efficiency, mid-shelf areas may have a high transfer efficiency, through the structuration of the planktonic food web (Marquis et al, 2011). The fact that similar ranges of biomass occur in the mid-shelf and over the slope, despite higher productivity over the slope, is potentially a sign of higher efficiency for the mid-shelf habitat.…”
Section: Productivity and Trophic Controlmentioning
confidence: 99%
“…Zooplankton are the intermediate trophic level between phytoplankton and fish and are an important component of carbon and nutrient cycles in the ocean. They account for a large proportion of the energy transfer to fish on continental shelves (Marquis et al, 2011), temperate reefs (Kingsford and MacDiarmid, 1988;Champion et al, 2015), seagrass meadows (Edgar and Shaw, 1995), and coral reefs (Hamner et al, 1988;Frisch et al, 2014). Zooplankton are also key in the transfer of energy between benthic and pelagic domains (Lassalle et al, 2013).…”
mentioning
confidence: 99%